Pengaruh Pelatihan Komunikasi Terapeutik terhadap Kepuasan Pasien : A Systematic Review - Agostinha Soares; Kusnanto Kusnanto; Ninuk Dian Kurniawati (FORIKES, 2020)
Background: Communication is an important element of quality care that can help build a nurse-patient relationship. Good nurse-patient communication has the potential to increase patient understanding of treatment plans and reduce behaviors that lead to poor outcomes. Not appreciating the importance of people-centered communication and improper communication training can result in unsatisfactory communication performance. Objective: Knowing the effect of therapeutic communication training on patient satisfaction Methods: The database used in this systematic review were taken from Scopus, Science direct, Proquest and Pubmed, journals were limited to the 2013-2019 publication year in the area of nursing medicine journals, as well as English journals. This systematic review used 9 articles that fitted the inclusion criteria. Critical appraisal and data extraction were performed independently by two different authors, there was a difference in results, the consensus was opted to solve the differences. Results: From 9 selected articles found that training varies between 50%-80% there was an influence on patient satisfaction. Therapeutic communication training had a positive impact on hospital services. Conclusion: Therapeutic communication training improves skills, encourages, supports, strengthens therapeutic communication, communication training reduces poor nurse interaction behavior and can increase patient satisfaction. Keywords: training; therapeutic communication; patient's satisfaction ABSTRAK Latar belakang: Komunikasi adalah elemen penting dari perawatan yang berkualitas dapat membantu membangun hubungan perawat-pasien. Komunikasi perawat-pasien yang baik memiliki potensi untuk meningkatkan pemahaman pasien tentang rencana perawatan dan mengurangi perilaku yang mengarah pada hasil yang buruk. Kurang menghargai pentingnya komunikasi yang berpusat pada orang dan pelatihan komunikasi yang tidak tepat dapat mengakibatkan kinerja komunikasi yang tidak memuaskan. Tujuan: Mengetahui pengaruh pelatihan komunikasi terapeutik terhadap kepuasan pasien Metode: Database yang digunakan dalam systematic review ini adalah scopus, science direct, proques dan pubmed, journal dibatasi dengan tahun publikasi 2013-2019 dengan area jurnal nursing medicine, serta jurnal berbahasa Inggris. Systematic review ini menggunakan 9 artikel yang sesuai dengan kriteria inklusi. Telaah artikel dan ekstraksi data dilakukan secara terpisah oleh dua peneliti, jika terdapat perbedaan, maka hasil diambil secara consensus. Hasil Dari 9 artikel terpilih ditemukan bahwa pelatihan bervariasi antara50%-80% ada pengaruh terhadap kepuasan pasien. Pelatihan komunikasi terapeutik memberikan dampak yang positif terhadap pelayanan rumah sakit. Simpulan: pelatihan komunikasi terapeutik meningkatkan keterampilan, mendorong, mendukung, memperkuat komunikasi terapeutik, pelatihan komunikasi mengurangi perilaku interaksi perawat yang buruk dan bisa meningkatkan kepuasan pasien Kata kunci: pelatihan; komunikasi terapeutik; kepuasan pasien